Recent Advances in Omega-3: Health Benefits, Sources, Products and Bioavailability (MDPI - Multidisciplinary Digital Publishing Institute, 2014)
The joint symposium of The Omega-3 Centre and the Australasian Section American Oil Chemists Society; Recent Advances in Omega-3: Health Benefits, Sources, Products and Bioavailability, was held November 7, 2013 in Newcastle, NSW, Australia. Over 115 attendees received new information on a range of health benefits, aquaculture as a sustainable source of supply, and current and potential new and novel sources of these essential omega-3 long-chain (LC, ≥C20) polyunsaturated fatty acid nutrients (also termed LC omega-3). The theme of "Food versus Fuel" was an inspired way to present a vast array of emerging and ground breaking Omega-3 research that has application across many disciplines. Eleven papers submitted following from the Omega-3 Symposium are published in this Special Issue volume, with topics covered including: an update on the use of the Omega-3 Index (O3I), the effects of dosage and concurrent intake of vitamins/minerals on omega-3 incorporation into red blood cells, the possible use of the O3I as a measure of risk for adiposity, the need for and progress with new land plant sources of docosahexaenoic acid (DHA, 22:6ω3), the current status of farmed Australian and New Zealand fish, and also supplements, in terms of their LC omega-3 and persistent organic pollutants (POP) content, progress with cheap carbon sources in the culture of DHA-producing single cell organisms, a detailed examination of the lipids of the New Zealand Greenshell mussel, and a pilot investigation of the purification of New Zealand hoki liver oil by short path distillation. The selection of papers in this Special Issue collectively highlights a range of forward looking and also new and including positive scientific outcomes occurring in the omega-3 field. [...]